Rosella Flower Dyes as A Substitute for Fuchsin - Sundari sundari (Jurnal Teknologi dan Manajemen Pengelolaan Laboratorium, 2020)
Along with the needs of quality preparations, of course the ingredients needed must be good, except the coloring preparations. Dyes that are widely used in practical activities are synthetic dyes. However, natural dyes from plants are preferred due to the efficiency in their use while working with the same function. Natural dyes are safer to use even though the degree of stability to heat, light and acidity is uncertain. The purpose of this study was to determine if rosella flower extract (Hibiscus sabdariffa) could be used as a substitute for fuchsin in Gram staining. This research was conducted by the experiments with laboratory scale using in vitro method. The results of the study concluded that rosella flower extract could not be used as natural dye for bacterial staining particularly for Staphylococcus aureus and E.coli bacterial preparations.